Combined growth hormone and insulin-like growth factor-1 rescues growth retardation in glucocorticoid-treated mdxmice but does not prevent osteopenia. Issue 2 (29th March 2022) - Wood, Claire L; van 't Hof, Rob; Dillon, Scott; Straub, Volker; Wong, Sze C; Ahmed, S Faisal; Farquharson, Colin
Abstract : Short stature and osteoporosis are common in Duchenne muscular dystrophy (DMD) and its pathophysiology may include an abnormality of the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis, which is further exacerbated by long-term glucocorticoid (GC) treatment. Hence, an agent that has anabolic properties and may improve linear growth would be beneficial in this setting and therefore requires further exploration. A 5-week-old x-linked muscular dystrophy ( mdx ) mice were used as a model of DMD. They were treated with prednisolone ± GH + IGF-1 for 4 weeks and then compared to control mdx mice to allow the study of both growth and skeletal structure. GC reduced cortical bone area, bone fraction, tissue area and volume and cortical bone volume, as assessed by micro computed tomography (CT) In addition, GC caused somatic and skeletal growth retardation but improved grip strength. The addition of GH + IGF-1 therapy rescued the somatic growth retardation and induced additional improvements in grip strength (16.9% increase, P   < 0.05 compared to control). There was no improvement in bone microarchitecture (assessed by micro-CT and static histomorphometry) or biomechanical properties (assessed by three-point bending). Serum bone turnover markers (Serum procollagen 1 intact N-terminal propeptide (P1NP), alpha C-terminal telopeptide (αCTX)) also remained unaffected. Further work is needed to maximise these gains before proceeding to clinical trials in boys with DMD.